Public History and the Digital Turn (The Russian Case) - Gagarina, Dinara; Imakaeva, Iliana (Public history weekly : blog journal for history and civics education, 2021)
Public and digital history in Russia is developing rather separately and in parallel to each other, these academic communities practically do not overlap. At the same time, a huge number of digital public history resources are being created. In the article, we consider some Russian features of public history in the context of digital turn, the actors of interaction between public and digital history, projects, as well as educational practices.<br
Keywords: Digital Change (Digitaler Wandel); Digital Humanities; Language: Russian; Russia (Russland)